The Serpent Column - Stephenson, Paul.
1 online resource (305 pages)
Keywords: Paul Stephenson twists together multiple strands to relate the cultural biography of a unique monument, the Serpent Column, which stands today in Istanbul 2,500 years after it was raised at Delphi.